Surface-selective laser sintering of thermolabile polymer particles using water as heating sensitizer. (30th November 2015) - Antonov, E N; Krotova, L I; Minaev, N V; Minaeva, S A; Mironov, A V; Popov, V K; Bagratashvili, V N
Abstract: We report the implementation of a novel scheme for surface-selective laser sintering (SSLS) of polymer particles, based on using water as a sensitizer of laser heating and sintering of particles as well as laser radiation at a wavelength of 1.94 μm, corresponding to the strong absorption band of water. A method of sintering powders of poly(lactide-co-glycolide), a hydrophobic bioresorbable polymer, after modifying its surface with an aqueous solution of hyaluronic acid is developed. The sintering thresholds for wetted polymer are by 3 – 4 times lower than those for sintering in air. The presence of water restricts the temperature of the heated polymer, preventing its thermal destruction. Polymer matrices with a developed porous structure are obtained. The proposed SSLS method can be applied to produce bioresorbable polymer matrices for tissue engineering.